Encouraging Residents to Request Wildlife-Friendly Landscape Maintenance from Their Chosen Professionals: A Stages of Change Approach for Extension and Other Practitioners: AEC795/WC456, 4/2024 - Warner , Laura A.; Kalauni, Dharmendra; Diaz , John M.; Marois, Emily; Dale , Adam; Daniels, Jaret (EDIS, 2024)
This publication explains Florida residents’ current involvement in requesting wildlife-friendly landscape maintenance (WFLM) and the perceived barriers and motivators associated with this behavior using the concept of stages of change. Written by Laura A. Warner, Dharmendra Kalauni, John M. Diaz, Emily Marois, Adam Dale, and Jaret Daniels, and published by the UF/IFAS Department of Agricultural Education and Communication, April 2024.